AKIBAT HUKUM KEDUDUKAN ANAK DALAM PERNIKAHAN SIRI DITINJAU DARI HUKUM ISLAM DAN UNDANG-UNDANG PERKAWINAN - I KADEK ADI SURYA (GANEC SWARA, 2023)
The goal to be achieved in this research is to find out the legal consequences of the position of children in unregistered marriages according to Islamic Law and the Marriage Law. To understand the concept of unregistered marriage according to Islamic Law and the Marriage Law. In this study the authors used the normative juridical writing method, namely legal research conducted using statutory regulations.According to Islamic law, an unregistered marriage is considered valid because a marriage that meets the pillars and conditions of marriage will be considered valid. Siri marriages are considered invalid according to the Marriage Law, because they refer to the provisions of Article 2 paragraph (2) of the Marriage Law regarding registration of marriages. From the provisions of this article, it can be seen that the Marriage Law focuses on the validity of marriage on two elements, namely; Marriage must be carried out in accordance with the conditions and procedures determined by law (state law) and religious law. This means that unregistered marriages that are carried out only by complying with religious law are not valid from the point of view of state law.For the legal status of children from unregistered marriages, according to Islamic law, they are considered legitimate children according to religion, because the child was born in or as a result of a legal marriage. According to the Marriage Law, the status of the child is the same as a child out of wedlock and cannot be said to be a child in a legal marriage, therefore the child does not have a birth certificate. As a result, legally the child has no right to claim support, inheritance or guardianship rights from his father. However, children from unregistered marriages can obtain their rights in accordance with Constitutional Court decision Number 46/PUU-VIII/2010 as long as they can prove it.